Rolling Path Plan of Mobile Robot Based on Automatic Diffluent Ant Algorithm - Zhou Feng (Institute of Advanced Engineering and Science, 2014)
This paper proposes a new rolling algorithm for path plan of mobile robot based on automatically shunt the ant algorithm.The goal node is mapped to the node nearby the boundary in the eyeshot of the robot, and make out the best partial path, which the robot goes ahead for a step. The algorithm will iterate one time when the robot arrives at the goal node. The robot will reach the destination along the optimal path. Simulation experiments illustrate that the algorithm can be used to plan the optimal path for mobile robot even in the complex and unknown static environment.